Reduced susceptibility to induced seizures in the Neuroligin-3R451C mouse model of autism. (4th March 2015) - Hill-Yardin, Elisa L.; Argyropoulos, Andrew; Hosie, Suzanne; Rind, Gil; Anderson, Paul; Hannan, Anthony J.; O'Brien, Terence J.
Highlights: Seizure susceptibility was examined in the Neuroligin-3 R451C mouse model of autism. Reduced susceptibility to tonic–clonic seizures in Neuroligin-3 R451C mice. Regional specific changes in the ratio of excitatory/inhibitory neurotransmission may influence seizure susceptibility to specific stimuli. Abstract: Epilepsy is a common comorbidity in patients with autism spectrum disorder (ASD) and several gene mutations are associated with both of these disorders. In order to determine whether a point mutation in the gene for the synaptic protein, Neuroligin-3 (Nlgn3, R451C), identified in patients with ASD alters seizure susceptibility, we administered the proconvulsant pentylenetetrazole (PTZ) to adult male Neuroligin-3 R451C (NL3 R451C ) and wild type (WT) mice. It has previously been reported that NL3 R451C mice show altered inhibitory GABAergic activity in brain regions relevant to epilepsy, including the hippocampus and somatosensory cortex. PTZ administration induces absence-seizures at low dose, and generalised convulsive seizures at higher dose. Susceptibility to absence seizures was examined by analysing the frequency and duration of spike-and-wave discharge (SWD) events and accompanying motor seizure activity induced by subcutaneous administration of low dosage (20 or 30 mg/kg) PTZ. Susceptibility to generalised convulsive seizures was tested by measuring the response to high dosage (60 mg/kg) PTZ using a modified Racine scale. There was no change in the number of SWD events exhibited by NL3 R451C compared to WT mice following administration of both 20 mg/kg PTZ (1.17 ± 0.31 compared to 16.0 ± 11.16 events/30 min, NL3 R451C versus WT, respectively) and 30 mg/kg PTZ (7.5 ± 6.54 compared with 27.8 ± 19.9 events/30 min, NL3 R451C versus WT, respectively). NL3 R451C mice were seizure resistant to generalised convulsive seizures induced by high dose PTZ compared to WT littermates (median latency to first >3 s duration clonic seizure; 14.5 min versus 7.25 min, 95% CI: 1.625–2.375, p  = 0.0009, NL3 R451C versus WT, respectively). These results indicate that the R451C mutation in the Nlgn3 gene, associated with ASD in humans, confers resistance to induced seizures, suggesting dysfunction of PTZ-sensitive GABAergic signalling in this mouse model of ASD.